Issues for Using All-Optical Wavelength Converters and Route Segmentation in Optical Networks - Tavares, Felipe A. S.; Fagotto, Eric A. M.; Abbade, Marcelo L. F. [UNESP]; Bonani, Luiz H. (Institute of Electrical and Electronics Engineers (IEEE), 2024)
In this paper, we present and numerically evaluate some issues on the performance of optical networks using route segmentation (RS) combined with all-optical wavelength converters (AOWCs). By considering modulation formats, fiber augmentation, and wavelength conversion, the study explores the impact of RS and AOWCs on network metrics, such as blocking rate (BR) and throughput. Simulations were conducted on the CORONET topology, analyzing various bandwidth parameter values for AOWCs. Results demonstrate that RS effectively reduces BR and enhances throughput, while AOWCs also improve performance. However, these two strategies must be balanced to match cost and performance requirements.
Keywords: All-Optical Wavelength Conversion; Optical Networks; Route Segmentation